A case of gastric adenocarcinoma of fundic gland type followed for 15 years - Odaka, Keita; Ikegami, Yurika; Watanabe, Ryo; Ito, Haruka; Yada, Tomoyuki; Yamanaka, Masahiro; Yagi, Toyokazu; Suzue, Koudai; Oide, Takashi; Uemura, Naomi; Mino, Masaaki; Nomiyama, Ai; et al. (Progress of Digestive Endoscopy, 2023)
A woman in her 80s underwent routine esophagogastroduodenoscopy (EGD). In X-9 year, a whitish mucosal lesion with dilated vessels was found on the posterior wall of the cardia. Biopsy examination showed that it was not malignant. In X year, biopsy examination of this lesion revealed gastric adenocarcinoma of the fundic gland type, and endoscopic submucosal dissection was performed. Upon reviewing previous endoscopic images obtained from the patient, the lesion was identified in an EGD image obtained in X-15 year. In X-11 year, the patient underwent H. pylori eradication therapy, but generally there was no significant change in endoscopic findings. We report a case of gastric adenocarcinoma of fundic gland type that was followed over a long period.